Improving the Photovoltage of Dithienopyrrole Dye‐Sensitized Solar Cells via Attaching the Bulky Bis(octyloxy)biphenyl Moiety to the Conjugated π‐Linker. (18th February 2013) - Cai, Ning; Zhang, Jing; Xu, Mingfei; Zhang, Min; Wang, Peng
Abstract The judicious design of 3D giant organic dye molecules to enable the formation of a porous photoactive layer on the surface of titania is one of the viable tactics to abate the adverse interfacial charge recombination in dye‐sensitized solar cells (DSCs) employing outer‐sphere redox couples. Here 2′, 6′‐bis(octyloxy)‐biphenyl substituted dithieno[3, 2‐b:2′, 3′‐d]pyrrole segment is constructed and employed as the π‐linker of a high molar absorption coefficient organic push‐pull dye. With respect to its congener possessing the hexyl substituted dithieno[3, 2‐b:2′, 3′‐d]pyrrole linker, the new dye can self‐assemble on the surface of titania to afford a porous organic coating, which effectively slow down the kinetics of charge recombination of titania electrons with both outer‐sphere tris(1, 10‐phenanthroline)cobalt(III) ions and photooxidized dye molecules, improving the cell photovoltage. In addition, the diminishments of charge recombination via modulating the microstructure of interfacial functional zone can also overcompensate the disadvantageous impact of reduced light‐harvesting and evoke an enhanced photocurrent output, bringing forth an efficiency improvement from 7.5% to 9.3% at the 100 mW cm−2, simulated AM1.5 conditions.